PRIORITY ISSUES OF THE DEVELOPMENT OF LEGAL EDUCATION IN THE REPUBLIC OF UZBEKISTAN - Boymirzaeva Rakhimaxon Khoshimjonovna (Bright Mind Publishing, 2025)
This article analyzes legal education, its specific features, the concept of legal education, and the expected results of legal education.
Keywords: Law, learner, legal education, legal consciousness, legal culture.